Guest Editorial: Mythical Identities, Scientific Realities, and Search for Transpersonal Meaning - Cunningham, Paul F (Journal of Scientific Exploration, 2023)
Myths weave in and out of historical context, even as dreams do relative to daily life, functioning in the modern world much as they did in earlier times, operating at both the personal and cultural levels. This essay discusses three special difficulties in appreciating the power of myth and understanding its reasons for being: (a) the nearly universal tendency to situate myth as the opposite of fact and truth, (b) the problem of identifying prevailing myths in culture and private life, and (c) the challenge of acknowledging myth as more than a personal intellectual construct or a cultural construction. Transpersonal theory offers a way forward in addressing these difficulties by placing personal and cultural myths and their relationship to historic–scientific fact in a greater context that endows them with greater meaning and reason for being than ordinarily appreciated by orthodox, mainstream Western psychology. Let us explore this premise detail.